National Hispanic Democratic Caucus Reception at Miles, Sears and Eanni - Watkins, Howard::::::::: (1988)
Justice Robert Martin, Robert Klein, Attorney General John Van de Kamp, Daniel Whitehurst, and Victor Moheno